2016
DOI: 10.3892/ol.2016.4606
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib induces lung cancer cell autophagy and apoptosis via blockade of the PI3K/AKT/mTOR pathway

Abstract: Gefitinib is a selective inhibitor of the tyrosine kinase epidermal growth factor receptor, which inhibits tumor pathogenesis, metastasis and angiogenesis, as well as promoting apoptosis. Therefore, gefitinib presents an effective drug for the targeted therapy of lung cancer. However, the underlying mechanisms by which gefitinib induces lung cancer cell death remain unclear. To investigate the effects of gefitinib on lung cancer cells and the mechanism of such, the present study analyzed the effect of gefitini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 38 publications
3
46
1
Order By: Relevance
“…Gefitinib induced apoptosis of NSCLC cells through direct inhibition of pro-survival p-EGFR, p-Akt, and p-Erk1/2 (Mukohara et al , 2005; Zhao et al , 2016b), which was also manifested in our study by gefitinib treatment in A549. On the other hand, LMB, as a specific CRM1 inhibitor of the nuclear export signal (NES)-dependent transport (Lu et al , 2015), was found to significantly upregulate the expressions of p-Erk1/2 and p-Akt in A549 in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Gefitinib induced apoptosis of NSCLC cells through direct inhibition of pro-survival p-EGFR, p-Akt, and p-Erk1/2 (Mukohara et al , 2005; Zhao et al , 2016b), which was also manifested in our study by gefitinib treatment in A549. On the other hand, LMB, as a specific CRM1 inhibitor of the nuclear export signal (NES)-dependent transport (Lu et al , 2015), was found to significantly upregulate the expressions of p-Erk1/2 and p-Akt in A549 in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…ERS shares a correlation with the PI3K/Akt/mTOR signaling pathway. Our experimental data revealed that increases in ERS are followed by decreases in PI3K/AKT/mTOR signaling, as well as reductions in chemoresistance; when the PI3K/AKT/mTOR signaling pathway is blocked, autophagy and apoptosis factors are increased, chemotherapy resistance is weakened, and the tumor shrinks [27, 59], which has an important function in autophagy and apoptosis regulation [2, 60, 61]. It has been reported that blocking the PI3K/AKT/mTOR cascade promotes autophagy [62] that inhibiting PI3K/Akt/mTOR signaling promotes cell apoptosis in LC [28], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most common malignant tumors worldwide, the leading risk factors involved with the occurrence of LC include both smoking as well as exposure and environmental factors [2]. The disease manifests itself with severe impairment of both patient health and quality of life [3].…”
Section: Introductionmentioning
confidence: 99%
“…8). In contrast, several studies have shown that blocking the Akt/mTOR pathway suppresses proliferation and promotes apoptosis in many kinds of tumors [38,39]. As mTOR controls cap-dependent translation [36], we hypothesize a possible mechanism whereby the activation of mTOR increases protein synthesis, which may then consume a lot of energy (ATP) and generate high levels of ROS.…”
Section: Discussionmentioning
confidence: 81%